The Influence of School Image, Facilities, and Price on Parents’ Decision to Choose Educational Services at Karya Senior High School Sekadau - Belembung, Elisabet; Ramadhan, Muhammad Ebuziyya Alif (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to analyze the influence of school image, facilities, and price on parents’ decision in choosing educational services at SMA Karya Sekadau. This research uses an associative quantitative method with a sample of 158 respondents determined using the Slovin formula. Data were collected through questionnaires and interviews, while data analysis was carried out using instrument validity and reliability tests, classical assumption tests, multiple linear regression analysis, as well as simultaneous F-test and partial t-test. The F-test results show that the variables of school image, facilities, and price simultaneously have a positive and significant effect on parents’ decisions. The t-test results also indicate that school image, facilities, and price each have a positive and significant partial effect on parents’ decisions. The coefficient of determination (R²) value of 0.523 indicates that 52.3% of parents’ decisions are influenced by these three variables. The implication of this study is that SMA Karya Sekadau needs to continuously strengthen its school image, improve the quality and adequacy of its facilities, and maintain transparency and affordability of costs to enhance competitiveness and public trust. This study recommends that future research expand the object of study, add other relevant variables, and use a mixed-methods approach for more in-depth results.